Maternal high‐fat diet‐induced programing of gut taste receptor and inflammatory gene expression in rat offspring is ameliorated by CLA supplementation. Issue 10 (22nd October 2015) - Reynolds, Clare M.; Segovia, Stephanie A.; Zhang, Xiaoyuan D.; Gray, Clint; Vickers, Mark H.
Abstract: Consumption of a high‐fat (HF) diet during pregnancy and lactation influences later life predisposition to obesity and cardiometabolic disease in offspring. The mechanisms underlying this phenomenon remain poorly defined, but one potential target that has received scant attention and is likely pivotal to disease progression is that of the gut. The present study examined the effects of maternal supplementation with the anti‐inflammatory lipid, conjugated linoleic acid (CLA), on offspring metabolic profile and gut expression of taste receptors and inflammatory markers. We speculate that preventing high‐fat diet‐induced metainflammation improved maternal metabolic parameters conferring beneficial effects on adult offspring. Sprague Dawley rats were randomly assigned to a purified control diet (CD; 10% kcal from fat), CD with CLA (CLA; 10% kcal from fat, 1% CLA), HF (45% kcal from fat) or HF with CLA (HFCLA; 45% kcal from fat, 1% CLA) throughout gestation and lactation. Plasma/tissues were taken at day 24 and RT‐PCR was carried out on gut sections. Offspring from HF mothers were significantly heavier at weaning with impaired insulin sensitivity compared to controls. This was associated with increased plasma IL‐1 β and TNF α concentrations. Gut Tas1R1, IL‐1 β, TNF α, and NLRP3 expression was increased and Tas1R3 expression was decreased in male offspring from HF mothers and was normalized by maternal CLA supplementation. Tas1R1 expression was increased while PYY and IL‐10 decreased in female offspring of HF mothers. These results suggest that maternal consumption of a HF diet during critical developmental windows influences offspring predisposition to obesity and metabolic dysregulation. This may be associated with dysregulation of taste receptor, incretin, and inflammatory gene expression in the gut. Abstract : The present study hypothesized that dietary supplementation with an anti‐inflammatory lipid, CLA, could dampen the metabolic inflammation induced by exposure to a high‐fat diet thereby preventing programing of obesity and its metabolic complications in the offspring. We examined the gut for markers relevant to inflammation and taste reception and found that maternal consumption of a HF diet during critical developmental windows influences offspring predisposition to obesity and metabolic dysregulation. This may be associated with dysregulation of taste receptor, incretin, and inflammatory gene expression in the gut.